2011
DOI: 10.1007/s11595-011-0346-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the aggregate volume on the electrical resistivity and properties of portland cement concretes

Abstract: The electrical resistivity of concretes with various aggregate volume fractions (V a ) of 0%-70% at water/cement (W/C) ratios of 0.4 and 0.5 during 1 day was monitored. It is found that the addition of normal aggregate to cement paste leads to a regular increase in concrete resistivity at each hydration stage and the electrical resistivity has a deeper increase for the lower W/C at a fi xed aggregate volume fraction. The number of normalized resistivity (NR) of concrete to its paste matrix was introduced, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…It illustrates that the bulk resistivity of the cement paste increases as the pore solution resistivity increases or porosity decreases. Wei and Xiao [27] observed the same trend of cement paste for the electrical resistivity development with time in concrete with various aggregate volume fractions, V a ; i.e., the curves dropped to a minimum point and then gradually increased with time which was governed by hydration process of its paste matrix. Therefore, they decided to study the relationship between electrical resistivity of concrete ρ C,t and paste matrix ρ P,t as a two component system; (1) aggregates (V a ) and (2) paste matrix (1-V a ).…”
Section: Relationship Between Bulk Electrical Resistivity and Pore Somentioning
confidence: 70%
See 4 more Smart Citations
“…It illustrates that the bulk resistivity of the cement paste increases as the pore solution resistivity increases or porosity decreases. Wei and Xiao [27] observed the same trend of cement paste for the electrical resistivity development with time in concrete with various aggregate volume fractions, V a ; i.e., the curves dropped to a minimum point and then gradually increased with time which was governed by hydration process of its paste matrix. Therefore, they decided to study the relationship between electrical resistivity of concrete ρ C,t and paste matrix ρ P,t as a two component system; (1) aggregates (V a ) and (2) paste matrix (1-V a ).…”
Section: Relationship Between Bulk Electrical Resistivity and Pore Somentioning
confidence: 70%
“…The types of aggregates were same for all the mixtures (i.e., the coarse and fine aggregates were made of granite and quartz, respectively). Wei and Xiao [27] observed that for each w/c ratio, increasing the aggregate volume fraction V a significantly increased the electrical resistivity; i.e., the higher the aggregate volume fraction, the higher the resistivity of concrete sample (see Fig. 2.22).…”
Section: Aggregate Volume Effect On the Electrical Resistivitymentioning
confidence: 95%
See 3 more Smart Citations